2013
DOI: 10.1111/apa.12262
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Japanese breastfed infants compared to national references and World Health Organization growth standards

Abstract: There were significant differences identified between the growth of breastfed infants and existing national references and WHO standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
5
20
0
Order By: Relevance
“…[11][12][13] Results from these studies showed that our newborns have smaller birth parameters compared to the WHO standard. For example, Japanese breastfed infants are significantly shorter and lighter throughout almost the first 24 months 12 compared to the WHO growth standard, and infants in Hong Kong are shorter at 36 months.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[11][12][13] Results from these studies showed that our newborns have smaller birth parameters compared to the WHO standard. For example, Japanese breastfed infants are significantly shorter and lighter throughout almost the first 24 months 12 compared to the WHO growth standard, and infants in Hong Kong are shorter at 36 months.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, studies from the East Asian countries have demonstrated a trend of smaller head circumference and birth weight. 12,13 Similarly, a Malaysian study in 1994 revealed that Malaysian infants were smaller than the standard reference. 8 The predictors of head circumference of infants have been widely studied.…”
mentioning
confidence: 99%
“…We excluded older studies (before 1988) comparing breastfed and formula-fed infants due to changes in formula content with time. A Japanese breastfed cohort was at least 0.5 SD below the MGRS mean at every age measured; means for formula-fed children were either within 0.25 SD of the MGRS mean or not below 0.5 SD 56. No pattern was found when comparing Greek breastfed infants with the national standards and MGRS data 57 80…”
Section: Resultsmentioning
confidence: 95%
“…This review uses studies from the following countries/ethnic groups: Argentina,44 Australia (indigenous and non-indigenous),28 49 75 Belgium,59 Brazil,41 Canada (indigenous and non-indigenous),10 48 77 China,65 71 Czech Republic,73 Denmark,16 52 66 Egypt,19 Euro-12,62 Finland,37 64 France,29 78 Germany13 50 79 Greece,57 80 Hong Kong,30 Iceland,53 81 India (birth and postnatal20 33 38 82 83), Iran,55 Ireland,84 Israel,34 Italy,31 85 Japan,14 39 56 Kuwait,43 Lebanon,36 Libya,86 Malaysia,35 Mexico,45 Moroccans (in the Netherlands and Spain),22 87 Nepal,63 the Netherlands (including Moroccans and Turks),18 87–90 New Zealand (indigenous and non-indigenous),58 91–93 Nigeria (birth26), Norway,12 51 67 Poland,94 95 Portugal,46 Russia,72 Saudi Arabia,25 Scotland,47 Singapore,40 69 South Korea,70 74 Spain (birth; Caucasians, Moroccans, South Americans and sub-Saharan Africans born in Spain),22 Spain (postnatal),96 Sweden,60 Switzerland,23 Taiwan,42 Turkey,21 90 United Arab Emirates,24 the UK54 and the USA,32 97 plus the MGRS 1 3. The participants in these studies totall...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation